2018
DOI: 10.3390/d10010010
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the Red Algal Laurencia Complex in the Macaronesia Region and Nearby Coastal Areas: Recent Advances and Future Perspectives

Abstract: Since the conception of the genus Laurencia by Lamouroux in 1813, several red macroalgal species have been included in it. In recent decades, the development of modern molecular tools has resulted in multiple taxonomic modifications, and presently, eight related genera are recognized in the so-called Laurencia complex. In the Macaronesian Region (Central East Atlantic Ocean), species from the Laurencia complex are keystone elements of the benthic communities, especially in the intertidal zone. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 68 publications
0
1
0
1
Order By: Relevance
“…A number of studies based on marine coastal fishes and gastropods from Cabo Verde concluded that the community structure and biogeographic relationships of its marine biota differ significantly from the other Macaronesian archipelagos 5,8,46–55 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies based on marine coastal fishes and gastropods from Cabo Verde concluded that the community structure and biogeographic relationships of its marine biota differ significantly from the other Macaronesian archipelagos 5,8,46–55 .…”
Section: Introductionmentioning
confidence: 99%
“…failed to detect this taxon. Likewise, the new species was not found in molecular diversity surveys of this group in Central American coasts (Stuerke & Freshwater 2008, 2010Mamoozadeh & Freshwater 2011, even if this region and Macaronesia often share the occurrence of species (Haroun & Prud'homme van Reine 1993;Machín-Sánchez et al 2018). While we cannot rule out that the new species could have remained unnoticed in these or other undersampled regions (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Out of 65 data deficient species 12 were macroalgae, whose alien status is debated among experts due to complexities in taxonomic identification, the existence of species complexes (e.g., the Laurencia complex [94,95]) or the possibility of Tethyan relicts (e.g., Acanthophora nayadiformis and Spyridia aculeata [96]). On the other hand, one characteristic example of a macroalgal species which was revised in the current inventory is Halophila decipiens.…”
Section: Species Validation and Uncertaintiesmentioning
confidence: 99%